Situation of music education in primary school in Wuhan (China). Analysis from the perspective of music teachers - Zhu, Qi; Solano-Sánchez, Miguel Ángel; Lorenzo Quiles, Oswaldo (Frontiers in Education, 2024)
This article makes an exploratory and diagnostic analysis, of empirical type, of the current situation of music education in primary schools in the city of Wuhan (China), from the perspective and opinion of the music teachers of these schools. The research approach is quantitative and a cross-sectional descriptive empirical-analytical research method was used. A total of 423 primary school music teachers from Wuhan participated in the research. An existing questionnaire on the situation of music education in primary schools in Beijing and Shanghai (China) is used in this research. This instrument has psychometric properties calculated by validity and reliability. As for the results of the questionnaire, the Mann–Whitney U-test was used to determine in which questions about the performance of music teachers in primary schools there are significant differences between different variables that make up the socio-demographic profile of the teacher, habits and resources available in the classroom. It is hoped that this study can contribute to the development of music education in Wuhan primary schools.